Analysis of Factors Causing Delay in Returning Inpatient Medical Record Files at Purwoharjo Health Center - Maya Weka Santi; Wiwik Dian Sari; Ida Nurmawati; Sabran Sabran (Saintika Medika : Jurnal Ilmu Kesehatan dan Kedokteran Keluarga, 2022)
Delays returning inpatient medical record files at the Purwoharjo Health Center reached 54.01%, far from the standard 100% return target within 2x24 hours after the patient returned home. The purpose of the study was analyzing the factors causing the delay in returning medical record files at the Purwoharjo Health Center. The research subjects were 8 informants. Collecting data using interviews, observation, documentation, priority problems with USG, and improvement planning to fix problems with FGD. The results of the analysis of the delay in returning inpatient medical record files due to lack of knowledge of officers on the standard of returning medical record files, indiscipline of officers in filling medical record files, SIMPUS often an error, non-optimal use of expedition books, incomplete filling of medical record files, patient motivation in the form of encouragement from medical record officers have been done but officers still often return medical record files delayed. Priority problems include incomplete filling of patient medical files, indiscipline in filling patient medical record files, and lack of motivation in the form of reward. Improvement planning is making SOP for filling the medical record, improving SOP for returning the medical record, posting SOP in every officer room, giving the reward.